Powerful Concepts in Global Health Comment on "Knowledge, Moral Claims and the Exercise of Power in Global Health" - Eivind Engebretsen; Kristin Heggen (Kerman University of Medical Sciences, 2015)
In this paper we emphasize the importance of questioning the global validity of significant concepts underpinning global health policy. This implies questioning the concept of global health as such and accepting that there is no global definition of the global. Further, we draw attention to 'quality' and 'empowerment' as examples of world-forming concepts. These concepts are exemplary for the gentle and quiet forms of power that underpin our reasoning within global health.